Isotopic and geochemical characterization of the metavolcano-sedimentary rocks of the Jirau do Ponciano Dome: A structural window to a Paleoproterozoic continental arc root within the Southern Borborema Province, Northeast Brazil - Lima, Haroldo M. (2019)
The Sergipano Fold Belt is a Neoproterozoic orogen exposed in the southern Borborema Province (Northeast Brazil), which is interpreted as the result of the oblique convergence process between the São Francisco-Congo block and smaller crustal fragments. The Nicolau-Campo Grande Complex is the metavolcanic-sedimentary portion of the Jirau do Ponciano Dome, an important basement inlier within this collisional belt. Whole-rockgeochemical major and trace-element data of major and trace elements from the metavolcanic rocks of the Nicolau-Campo Grande Complex indicate basaltic-andesite, andesitic, rhyodacitic, and rhyolitic compositions. Rare earth element and trace elements show the typical signature of magmatic arc rocks with negative Nb, Ta, P, and Ti anomalies. New U-Pb zircon data from amphibolite and hornblende-biotite paragneiss samples from the complex confirm the existence of a Paleoproterozoic zircon population of a Paleoproterozoic age of approximately ca. 2054 Ma with Archean inheritance ranging in age between 2779 and 3324 Ma. A maximum sedimentation age of 2028 Ma is constrained by the youngest zircon grain in the hornblende-biotite paragneiss. Zircon U-Pb data from the metarhyolite and rhyodacites indicate Paleoproterozoic ages of ca. 2061 and 2074 Ma, respectively, interpreted as their crystallization age. Nd isotopic data in the metarhyolite and rhyodacites indicate Nd TDM ages between 2.54 and 3.07 Ga and 87Sr/86Sr (2061Ma) values from 0.71396 to 0.72351. Based on these data, we suggest that the probable source area of the metavolcanic-sedimentary complex is a Paleoproterozoic magmatic arc that was exhumed and covered by the paleobasins of the Macururé Domain in the northeast portion of the Sergipano Fold Belt.